Management problems as a factor of influence on the socio-political and economic situation in the Rostov region - V. S. Semenov (Современная наука и инновации)
The article contains consolidated ideas and analytical conclusions regarding general and specific problems of management activities in the Rostov region, as a key region of the South of Russia. The importance of administrative and organizational measures in maintaining stability and developing the sociopolitical and economic situation is explored, in particular, in the context of the deployment of the SVO and increased sanctions pressure. Separate proposals for optimizing the processes under consideration are formulated.